ARTIs Prevention Efforts at Paya Lebar Village - Nurningsih Sinuraya; Rachmawaty M. Noer; Sherly Mutiara; Endah Hapsari; Neni Triana; Istini (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
[1] Andanawarih, P., & Baroroh, I. (2018). The Role of Midwives as Facilitators for the Implementation of the Maternity Planning and Complication Prevention Program (P4k) in the Pekalongan District Health Center Area. Cycle: Journal of Tegal Polytechnic Midwifery Research, 7 (1) : 252-256. [2] Ministry of Health of the Republic of Indonesia, 2002, Guidelines for the Eradication of Acute Upper Respiratory Infection for Prevention of Pneumonia in Toddlers in Pelita VI , Ministry of Health of the Republic of Indonesia, Jakarta. [3] Ministry of Health of the Republic of Indonesia. Riskesdas Indonesia 2007 . jakarta: 2007 . [4] Ministry of Health of the Republic of Indonesia. 2004. Guidelines for the eradication ofacute respiratory infections (ISPA) to controlpneumonia in children under five. Jakarta: MOH RI. [5] Ministry of Health of the Republic of Indonesia, 2014a, Clinical Practice Guide for Doctors in Primary Health Care Facilities , Ministry of Health of the Republic of Indonesia, Jakarta. [6] Ministry of Health of the Republic of Indonesia, 2014b, Indonesia Health Profile 2013 , Ministry of Health of the Republic of Indonesia, Jakarta. [7] Nurrijal, (2009) . Acute Respiratory Infections . http: //www.springerlink.com (23 August 2014 ) [8] Papilaya, EA, ZuliAri, K., &. J. (2016). Comparison of the effect of health promotion using audio-visual media with audio-visual media on elementary students' oral health behavior. E-TEETH, 4 (2): 282-286. [9] Sanjaya, Vienna. 2009. Process-Oriented Learning Strategy Standards. Education. Jakarta : Prenada [10] Somantri, I., 2008, Medical Surgical Nursing: Nursing Care for Patients with Respiratory System Disorders , Salemba Medika, Jakarta. [11] Susilo, A., Rumende, CM, Pitoyo, CW, Santoso, WD, Yulianti, M., Herikurniawan, H., Sinto, R., Singh, G., Nainggolan, L., Nelwan, EJ, Chen, LK, Widhani, A., Wijaya, E., Wicaksana, B., Maksum, M., Annisa, F., Jasirwan, COM, & Yunihastuti, E. (2020).